2015
DOI: 10.1146/annurev-cellbio-100814-125234
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Regulation, and Functional Diversity of Microvilli on the Apical Domain of Epithelial Cells

Abstract: Microvilli are actin-based structures found on the apical aspect of many epithelial cells. In this review, we discuss different types of microvilli, as well as comparisons with actin-based sensory stereocilia and filopodia. Much is known about the actin-bundling proteins of these structures; we summarize recent studies that focus on the components of the microvillar membrane. We pay special attention to mechanisms of membrane microfilament attachment by the ezrin/radixin/moesin family and regulation of this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
158
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(169 citation statements)
references
References 235 publications
(285 reference statements)
6
158
1
1
Order By: Relevance
“…3C, arrows), consistent with actin filaments that are typically found in microvilli lining the luminal space in epithelial tissues. However, unlike typical microvilli, which given a certain cell type adopt a consistent shape and length within the same cell (Sauvanet et al, 2015), we found membrane protrusions of various lengths, some of which were branched, further indicating that their architecture could be more complex.…”
Section: Membrane Protrusions In the Intercellular Space Form An Extecontrasting
confidence: 55%
“…3C, arrows), consistent with actin filaments that are typically found in microvilli lining the luminal space in epithelial tissues. However, unlike typical microvilli, which given a certain cell type adopt a consistent shape and length within the same cell (Sauvanet et al, 2015), we found membrane protrusions of various lengths, some of which were branched, further indicating that their architecture could be more complex.…”
Section: Membrane Protrusions In the Intercellular Space Form An Extecontrasting
confidence: 55%
“…5), which are convoluted apical membrane extensions with cores of crosslinked actin bundles. Microvilli are also found in other polarized epithelia and excellent reviews on microvillar biology are available (Crawley et al, 2014;Sauvanet et al, 2015). Here, we focus on the intestinal phenotypes of relevant mouse models and human conditions in which microvillus structure is perturbed.…”
Section: Formation Of the Microvillar Brush Bordermentioning
confidence: 99%
“…Here, we focus on the intestinal phenotypes of relevant mouse models and human conditions in which microvillus structure is perturbed. Microvillus formation begins when actin filaments nucleate at electron-dense plaques in the apical actin terminal web (Crawley et al, 2014;Sauvanet et al, 2015). The actin-bundling protein villin is first expressed at E10 and becomes apically concentrated by E13.5 (Ezzell et al, 1989) where it crosslinks and stabilizes actin fibers.…”
Section: Formation Of the Microvillar Brush Bordermentioning
confidence: 99%
See 1 more Smart Citation
“…Microvilli line the apical surface of epithelial cells forming a densely packed structure known as the brush border in tube-like tissues, such as intestines, kidney, and lung (2)(3)(4)(5). The best known function of microvilli is to massively increase membrane surface area of these tissues to promote solute exchange, although these protrusions may also allow cells to communicate with their extracellular surroundings (6).…”
mentioning
confidence: 99%